2011
DOI: 10.1590/s1516-14392011005000081
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical degradation and VOC emission of unstabilized and stabilized polypropylene copolymer during multiple Extrusions

Abstract: The thermo-mechanical degradation during the multi-extrusion of unstabilized and stabilized polypropylene copolymer (cPP) was analyzed using the Chain Scission Distribution Function (CSDF) method. During the first extrusion of unstabilized cPP almost 60% of the initial polymeric chains were submitted to chain scission. The calculations using CSDF show a random chain scission process of chains with molecular weight below 100 kg.mol -1 , and above that a preferential chain scission process. When stabilized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Caceres et. al [39] studied the chain scission PP degradation during multiple extrusions. Epacher et al [40] and Santoz et al [41] indicated the positive effects of Irganox 1010 and Irganox 168 as antioxidants for stabilization of HDPE and PP/PE polyolefins during multiple extrusions by considering degradation.…”
Section: Effect Of Wf Content On the Mechanical And Physical Propertimentioning
confidence: 99%
“…Caceres et. al [39] studied the chain scission PP degradation during multiple extrusions. Epacher et al [40] and Santoz et al [41] indicated the positive effects of Irganox 1010 and Irganox 168 as antioxidants for stabilization of HDPE and PP/PE polyolefins during multiple extrusions by considering degradation.…”
Section: Effect Of Wf Content On the Mechanical And Physical Propertimentioning
confidence: 99%
“…Although plenty of studies have recently investigated the processability of complex recycled regional postconsumer waste by FFF and have even recommended the use of so-called RecycleBots [38,39,40], such as blends of polyethylene [39,41,42,43,44,45], polypropylene (PP) [44,46,47,48,49,50], polyethylene terephthalate (PET) [49,50,51], acrylonitrile butadiene styrene (ABS) [49,52], poly(lactic acid) (PLA) [49,53], polystyrene (PS) [50], polyvinyl alcohol (PVA) [54], or polyamide (PA) [55], the effect of multiple AM and filament extrusion sequences on the processability of materials more complex than the standard FFF material PLA, which is known to be susceptible to thermal degradation [9], has not yet been studied. Moreover, neither the positive effect of thermal stabilizers on retaining mechanical strength [56] nor the degradation of a filler–matrix interface with increasing re-extrusion cycles [57] has been confirmed for advanced composites used in FFF.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, FTIR and NMR are popular methods for degradation characterization; however, they can be ineffective at defining small structural changes [139]. Furthermore, sometimes the oxygen content inside the extruder is low enough to avoid the formation of measurable carbonyl quantities by the FTIR technique [159]. Therefore, upon studying low extents of degradation as in the context of mechanical recycling, rheometry and chromatography may be the most sensitive tools in identifying the molecular changes.…”
Section: Molecular Properties Characterizationmentioning
confidence: 99%
“…The influence of single extrusion, multiple extrusion, AM, and injection molding on polymeric degradation has been broadly studied in the past decades. For instance, degradation has been assessed for PLA and PLLA [167,[173][174][175][176], poly(ethylene terephthalate) (PET) [177,178], PS [42,[179][180][181], ABS [182][183][184], HIPS [185][186][187], PP [93,151,159,[188][189][190][191], HDPE [139,188,192], LDPE [140], and poly(methyl methacrylate) (PMMA) [42]. To highlight the advances made, an overview of the most important findings is given in this section.…”
Section: Manufacturing Case Studies To Assess Degradabilitymentioning
confidence: 99%